Effect of partially demineralized dentin beneath the hybrid layer on dentin-adhesive interface micromechanics - Anchieta, Rodolfo Bruniera [UNESP]; Machado, Lucas Silveira [UNESP]; Sundfeld, Renato Herman [UNESP]; Reis, Andre Figueiredo; Giannini, Marcelo; Luersen, Marco Antonio; Janal, Malvin; Rocha, Eduardo Passos [UNESP]; Coelho, Paulo G. (Elsevier B.V., 2015)
Objective: To investigate the presence of non-infiltrated, partially demineralized dentin (PDD) beneath the hybrid layer for self-etch adhesive systems, and its effect on micromechanical behavior of dentin-adhesive interfaces (DAIs). This in-vitro laboratory and computer simulation study hypothesized that the presence of non-infiltrated PDD beneath the hybrid layer does not influence the mechanical behavior of the DAI of self-etch adhesive systems.Methods: Fifteen sound third molars were restored with composite resin using three adhesive systems: Scotchbond Multipurpose (SBMP), Clearfil SE Bond (CSEB) and Adper Promp L-Pop (APLP). The thickness and length of all DAIs were assessed using scanning electron microscopy, and used to generate three-dimensional finite element models. Elastic moduli of the hybrid layer, adhesive layer, intertubular dentin, peritubular dentin and resin tags were acquired using a nano-indenter. Finite element software was used to determine the maximum principal stress. Mixed models analysis of variance was used to verify statistical differences (P < 0.05).Results: Elastic moduli and morphology were found to differ between the adhesive systems, as well as the presence and extension of PDD.Significance: Both self-etch adhesive systems (APLP and CSEB) had PDD. The DAI stress levels were higher for the one-step self-etch adhesive system (APLP) compared with the etch-and-rinse adhesive system (SBMP) and the self-etch primer system (CSEB). (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Dentin; Adhesive systems; Mechanical properties; Finite element; Adhesion; Nano-indentation; Hybrid layer